Perbandingan Prestasi Akademik Mahasiswa Jurusan Biologi Jalur PMJK/PMDK dengan SPMB - Hamka, Lodang; Muhiddin, Palennari (bionature, 2010)
This study aims to determine academic achievement of biology student  PMJK/PMDK, knowing academic achievement of biology students SPMB and find the differences between academic achievement of biology students' PMJK/PMDK with SPMB. Kind of research is ex post facto research with the population are biology student whole  academic year 2008/2009 and samples include (1) Line SPMB taken by way of purposive sampling as many as 168 students of class 2005, 2006 and 2007. (2) Line PMJK taken entirely in force in 2005, 2006 and 2007 are still active that is counted 168 people. Data collection techniques using secondary data is student GPA data 2005, 2006 and 2007. GPA is calculated until the second semester academic year 2008/2009. Further data are analyzed quantitatively with percentages and inferential analysis with t test. The results of analysis of research data obtained by the average GPA of students and PMK SPMB line is 2.958 and the result t-test = 0:01, P = 0999. The research concluded that academic achievement of  biology student  PMJK/ PMDK and SPMB  is very satisfy category with average GPA = 2,958 and there was no difference academic achievement of biology student PMJK/PMDK and SPMB.